Loss of CD169+ Subcapsular Macrophages during Metastatic Spread of Head and Neck Squamous Cell Carcinoma. (July 2019) - Topf, Michael C.; Harshyne, Larry; Tuluc, Madalina; Mardekian, Stacey; Vimawala, Swar; Cognetti, David M.; Curry, Joseph M.; Rodeck, Ulrich; Luginbuhl, Adam
Objective: The purpose of this study is to assess CD169 expression in metastatic and nearby tumor-free lymph nodes of patients with head and neck squamous cell carcinoma (SCC). Study Design: Retrospective analysis based on immunohistochemistry. Setting: Tertiary care center. Subjects and Methods: The abundance of CD169 + cells in the subcapsular sinuses (SCSs) of lymph nodes was assessed immunohistochemically in paraffin-embedded tissue samples derived from 22 patients with oral cavity and oropharyngeal SCC. Results: SCSs of lymph nodes harboring metastatic SCC contained significantly fewer CD169 + macrophages (106.5 ± 113.6 cells/mm 2 ) compared to nearby tumor-free lymph nodes (321.3 ± 173.4 cells/mm 2, P < .001). This observation extended to 21 of the 22 cases investigated. In addition, 6 patients who later developed recurrent disease contained lower numbers of CD169 + cells (268.6 ± 169.5 cells/mm 2 ) in nearby tumor-free lymph nodes compared to 341.0 ± 176.1 cells/mm 2 in those who remained disease free ( P = .399). Human papillomavirus (HPV)–positive patients (n = 4) had a 6-fold lower number of CD169 + cells in metastatic nodes (61.2 ± 85.5 cells/mm 2 ) compared to nearby tumor-free lymph nodes (369.5 ± 175.5 cells/mm 2, P = .028). In comparison, HPV-negative patients had only a 3-fold reduction (116.6 ± 118.5 cells/mm 2 vs 310.6 ± 176.2 cells/mm 2, P < .001). Conclusion: Metastatic spread of SCC to regional lymph nodes is associated with lower abundance of CD169 + macrophages in the SCSs of draining lymph nodes. These results set the stage for an in-depth investigation into the mechanism(s) by which metastatic SCC controls CD169 + macrophage abundance and its significance as it relates to prognosis and treatment response.